Taking the ruler to the jungle: single-molecule FRET for understanding biomolecular structure and dynamics in live cells. (October 2015) - Sustarsic, Marko; Kapanidis, Achillefs N
Highlights: Single-molecule FRET can be applied inside live cells. Optimal labeling, internalization and imaging strategies are being developed. smFRET detection has been demonstrated in both microbial and mammalian systems. Biomolecular structure and dynamics can be studied. Abstract : Single-molecule Förster resonance energy transfer (smFRET) serves as a molecular ruler that is ideally posed to study static and dynamic heterogeneity in living cells. Observing smFRET in cells requires appropriately integrated labeling, internalization and imaging strategies, and significant progress has been made towards that goal. Pioneering studies have demonstrated smFRET detection in both prokaryotic and eukaryotic systems, using both wide-field and confocal microscopies, and have started to answer exciting biological questions. We anticipate that future technical developments will open the door to smFRET for the study of structure, conformational changes and kinetics of biomolecules in living cells.